Pesticides in the population of European hedgehogs (Erinaceus europaeus) in Denmark - Rasmussen, Sophie Lund; Roslev, Peter; Nielsen, Jeppe Lund; Pertoldi, Cino; Vorkamp, Katrin (Frontiers in Veterinary Science, 2024)
European hedgehogs (Erinaceus europaeus) inhabit most of Denmark, except for a few smaller islands. Research from other European countries has shown that the hedgehog populations are in decline. The exposure to chemicals might contribute to this development, although their role is currently unknown.Our research studied the occurrence of 19 selected pesticides in the Danish hedgehog population as well as factors potentially explaining the levels of chemicals detected.We analysed 115 liver samples obtained from dead hedgehogs in 2016 for seven rodenticides, four insecticides and eight herbicides commonly used in Denmark at the time of sampling, applying a high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) method.Detection frequencies varied between 0.9% for fluroxypyr and trans-permethrin and 79% for bromadiolone. Rodenticides, insecticides and herbicides were detected in 84, 43 and 50% of the samples, respectively. The compounds most frequently detected included the insecticide imidacloprid (35%), the herbicide metamitron (29%) and the rodenticide bromadiolone (79%). Individual concentrations varied between non-detected to > 2 µg/g. A total of 79% of the 115 hedgehogs contained more than one detectable pesticide, with up to nine of the 19 compounds detected in one individual.The detection frequencies were found to differ significantly between the Eastern and Western part of Denmark for difenacoum, difethialone and imidacloprid. However, no associations were found with sex, age, habitat type or the prevalence of mecC-MRSA and endoparasites in the hedgehogs tested.Whether or not the pesticide levels detected carry a health risk for the hedgehogs remains unknown as no adverse effect levels have yet been established for European hedgehogs for single compounds or pesticide mixtures.